Correlated Factors on Performance of Tuberculosis Program Officers at Community Health Clinic in Increasing the Finding of New AFB Smear-Positive Cases (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
ABSTRACT Semarang regency had CDR issues under the national target. The activity of new cases finding determine the success of the tuberculosis eradication programs, so the process of find new AFB smear-positive cases by officers is crucial. The purpose of this study was to determine factors related to the performance of tuberculosis officers at the community health clinic in increasing the findingof AFB smear-positive new cases (case study in Semarang regency). This type of research is observational analytic, with the cross-sectional design involving 45 saturated samples. Data analysis used was chi-square test. The results showed that factors related to the performance of tuberculosis programs officers were knowledge (p = 0.022), training (p = 0.001), double duty (p = 0.014), screening for active TB suspect (p = 0.038), motivation (0.040) and attitude (p = 0.011). While there was no correlation between years of service (p = 0.152), facilities (p = 0.154), and incentive (p = 0.121). ABSTRAK Kabupaten Semarang memiliki permasalahan CDR di bawah target nasional. Kegiatan penemuan kasus baru menentukan keberhasilan program pemberantasan tuberkulosis, sehingga proses penemuan kasus baru BTA positif oleh petugas sangat menentukan. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan kinerja petugas tuberkulosis puskesmas dalam meningkatkan penemuan kasus baru BTA positif (studi kasus di Kabupaten Semarang). Jenis penelitian ini adalah analitik observasional, dengan desain cross sectional yang melibatkan 45 sampel jenuh. Analisis data menggunakan uji chi square. Hasil penelitian menunjukkan faktor yang berhubungan dengan kinerja petugas program tuberkulosis puskesmas adalah pengetahuan (p = 0,022), pelatihan (p = 0,001), tugas rangkap (p = 0,014), penjaringan suspek TB aktif (p = 0,038), motivasi (0,040), dan sikap (p = 0,011). Sementara tidak ada hubungan antara faktor masa kerja (p = 0,152), sarana (p = 0,154), dan insentif (p = 0,121).